2023
DOI: 10.18632/aging.204971
|View full text |Cite
|
Sign up to set email alerts
|

miR-100-5p activation of the autophagy response through inhibiting the mTOR pathway and suppression of cerebral infarction progression in mice

Xiaoyun Cao,
Xiangjian Zhang,
Junmin Chen
et al.

Abstract: In recent years, the association between microRNAs (miRNAs) and autophagy in cerebral infarction (CI) has attracted increasingly more attention. The mammalian target of the rapamycin (mTOR) pathway is a key protein regulating the autophagy response. miR-100-5p can bind to the mTOR protein, but its role in CI remains unclear yet. This experiment aims to clarify the role of miR-100-5p in CI. Bioinformatics analysis was performed to screen differentiated expressed functional genes between CI tissue and normal tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Our study revealed that leptin could play an important role in spermatogenesis through the regulation of mTOR. mTOR is a key regulator of cellular homeostasis and metabolism, controlling many biological processes such as amino acid synthesis, glucose metabolism, cytoskeleton organization and so on 24,25 . Spermatogenesis is a continuous process, which involves the proliferation and differentiation of spermatogonia.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that leptin could play an important role in spermatogenesis through the regulation of mTOR. mTOR is a key regulator of cellular homeostasis and metabolism, controlling many biological processes such as amino acid synthesis, glucose metabolism, cytoskeleton organization and so on 24,25 . Spermatogenesis is a continuous process, which involves the proliferation and differentiation of spermatogonia.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that certain miRNAs modulate autophagy through various pathways. For example, miR-100-5p has been shown to promote autophagy and inhibit apoptosis by regulating mTOR (a key regulator of autophagy) [ 64 ]. miR-15b-5p and miR-424-5p compete for binding to plasmacytoma variant translocation 1 (PVT1), resulting in the promotion of autophagy and the downregulation of apoptosis [ 65 ].…”
Section: Interaction Mechanisms Of Ibs and Ncrnamentioning
confidence: 99%